1999
DOI: 10.1152/ajpregu.1999.276.3.r724
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine stimulates lymphoid cell mobilization from the perfused rat spleen via β-adrenergic receptors

Abstract: The possibility that norepinephrine (NE) influences lymphoid cell outflow independently of its vasoconstrictor action was investigated in the perfused rat spleen. Using agents that affect the vasoconstrictor tonus of the spleen, we observed an inverse correlation between flow resistance and splenic cell output. The curve obtained served as a reference for evaluating effects of different treatments on the number of cells that are mobilized at defined levels of flow resistance. Perfusion of the β-adrenergic bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Furthermore, coadministration of epinephrine that normally counteracts the cardiovascular suppression induced by propranolol augmented the effect of this drug on the survival and on cellular immune functions. In addition, it was demonstrated that a ß-adrenergic blockade with or without the concomitant administration of an ·-adrenergic agonist did not increase the vascular resistance of the spleen [26]. We therefore assume that the increased mortality after the ß-adrenergic blockade in our experiment was mainly due to the observed immunologic changes rather than the consequence of local or systemic cardiovascular changes.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, coadministration of epinephrine that normally counteracts the cardiovascular suppression induced by propranolol augmented the effect of this drug on the survival and on cellular immune functions. In addition, it was demonstrated that a ß-adrenergic blockade with or without the concomitant administration of an ·-adrenergic agonist did not increase the vascular resistance of the spleen [26]. We therefore assume that the increased mortality after the ß-adrenergic blockade in our experiment was mainly due to the observed immunologic changes rather than the consequence of local or systemic cardiovascular changes.…”
Section: Discussionmentioning
confidence: 58%
“…Infusion of catecholamines into the spleen increases leukocyte output by either β-or α-AR mediated mechanisms in the absence of changes in blood flow [273]. Besedovsky and colleagues [274] have demonstrated that sympathetic innervation of the spleen alters flow resistance to affect leukocyte output from the spleen. Collectively these studies support a role for the SNS in regulating the cell entry, retention, and release from lymphoid organs.…”
Section: Functional Significance Of Sympathetic Innervation Of Secondmentioning
confidence: 99%
“…3). In particular, catecholamines induce elevation in the number of circulating lymphocytes both in humans (4) and mice (5). The global effect of b-agonists on immunity was mainly studied by chemically depleting natural catecholamine stocks using 6-hydroxydopamine, which results in increased innate immune responses against bacteria (6), increased adaptive immune responses against virus (7), and decreased immune responses against Gram-positive bacteria (7)(8)(9).…”
mentioning
confidence: 99%